PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN MATEMATIKA DI SDN CIBULUH 6 KOTA BOGOR - Raden Enah Hasanah (Universitas Pakuan, 2021)
APPLICATION OF THE NUMBERED HEADS TOGETHER (NHT) COOPERATIVE LEARNING MODEL TO IMPROVE STUDENTS' LEARNING OUTCOMES IN MATHEMATICS SUBJECTS IN ELEMENTARY SCHOOLS (SDN CIBULUH 6 KOTA BOGOR)This research departs from the phenomenon that occurs in the classroom that the students' understanding and learning outcomes are low in mathematics learning about comparing and sorting fractions. Therefore, a teacher needs to consider learning strategies so that they can improve student learning outcomes. This research was carried out in Class IV of Elementary School (SD Negeri Cibuluh 6) and aimed (1) To find out the application of the Numbered Heads Together (NHT) Cooperative learning model can improve student learning outcomes in mathematics subjects about comparing and sorting fractions in class IV A Elementary School (SD Negeri Cibuluh 6). (2) To define the process of improving student learning outcomes in mathematics subjects about comparing and sorting fractions after using the Numbered Heads Together learning model. (3) To measure the magnitude of the increase in student learning outcomes in mathematics subjects about comparing and sorting fractions after using the Numbered Heads Together Type of Cooperative learning model. The results of this study indicate that using the Numbered Heads Together Cooperative learning model can be a fun variation of learning for students so that it is proven to improve student learning outcomes. Before the Numbered Heads Together Type Cooperative learning model, student learning outcomes only reached an average value of 66.15 then there was an increase after using the Numbered Heads Together Cooperative learning model to 74.61 in cycle 1 and 81.79 in cycle 2. Research results concluded that the use of the Numbered Heads Together Cooperative learning model which is adapted to the learning material can create a pleasant learning situation so that there is an increase in student learning outcomes. Therefore, the researchers suggest that the use of the Numbered Heads Together Cooperative learning model is socialized and used as an alternative in learning mathematics in schools within the Bogor City Education Office.